Aspergillus fumigatus infection as a delayed manifestation of prosthetic knee arthroplasty and a review of the literature - Yılmaz, Mesut; Mete, Bilgül; Özaras, Reşat; Kaynak, Gökhan; Tabak, Fehmi; Tenekecioğlu, Yüksel; Öztürk, Recep (Informa Healthcare, 2011)
Fungal infection after total joint arthroplasty is a very rare but serious complication and a challenge to the treating and consulting physicians. The literature includes little information about the treatment protocol for Aspergillus infection after total knee arthroplasty, since only 3 cases have been reported. We describe the case of a non-immunocompromised patient who lacked predisposing risk factors and presented with pain and swelling. An aspiration under sterile conditions revealed Aspergillus fumigatus. The patient was treated successfully with a 2-stage exchange reimplantation and 6-week course of liposomal amphotericin B. At 4 y after reimplantation, the patient had no evidence of infection or pain.
WOS: 000292777800002
PubMed ID: 21526903
Keywords: Aspergillus Fumigatus; Prosthetic Infection; Total Knee Arthroplasty; Amphotericin B